Association of Diabetes Mellitus and Vulvovaginal Candidiasis : A Systematic Review - Karina Maharati Wibowo; Elsi Septira Wibowo (The International Journal of Medical Science and Health Research, 2025)
Introduction: Diabetes Mellitus (DM) is a global pandemic that significantly increases susceptibility to infections, including Vulvovaginal Candidiasis (VVC). This increased risk is attributed to hyperglycemia and compromised immune function. VVC in diabetic women often presents with greater severity, recurrence, and treatment challenges. This systematic review synthesizes the current evidence on the association between DM and VVC. Methods: This review followed PRISMA 2020 guidelines. A systematic search was conducted across PubMed, Springer, Semantic Scholar, and Google Scholar to identify relevant studies. Eligibility criteria focused on observational studies and reviews examining VVC in adult females with Type 1 or Type 2 diabetes. After screening, 27 articles were included for analysis. Results: The evidence confirms a significantly higher prevalence of VVC in diabetic women (32-67.5%) compared to non-diabetic women (11-23%). The risk is elevated in both Type 1 DM (84% prevalence) and Type 2 DM (68% prevalence) versus controls (27%). Poor glycemic control is a critical factor, with VVC prevalence doubling in uncontrolled (31.4%) versus controlled (15.7%) diabetes. VVC in diabetics is associated with higher recurrence and increased infections by non-albicans Candida species, which are often resistant to standard azole antifungals. Conclusion: The association between DM and VVC is robust and deeply rooted in the pathophysiological effects of hyperglycemia and immune dysfunction. The cornerstone of prevention and management is rigorous glycemic control. The clinical approach must be integrated, addressing both the infection with appropriate, sometimes alternative, antifungal therapies and the underlying metabolic disorder to reduce the burden of this common and challenging comorbidity.